Emerging Environmental Ethics for Living with Novel Fire Regimes in the Blue Ridge Mountains - Cynthia T. Fowler (Ethnobiology Letters, 2018)
This article focuses on anthropogenic fire as a form of disturbance that is having an unusually strong influence on landscapes in the Blue Ridge Physiographic Province of the Southern Appalachian Mountains. One series of significant disturbance incidents was the Blue Ridge Complex, which was a dense cluster of wildfires that occurred during the fall of 2016. This article contains ethnographic information that I collected when the Blue Ridge Complex fires were burning and thereafter through the use of participant observation at community gatherings, land management events, and recreational activities. I have also conducted one-on-one interviews with residents of the fire-affected region, land managers, and firefighters. In community gatherings and in conversations with others, people living in the Blue Ridge Complex zone produced a collective ethical assemblage for living in a burning and burned landscape. The spatial and temporal patterns of burning in the fall of 2016 were so distinct from previous years that they may have redefined the Blue Ridge bioregion’s fire regimes. The proliferation of wildfires during the fall of 2016 also generated occasions for people to formulate their values related to one another, to their nonhuman co-residents, to fire, and to the overall mountainous landscape.